39Ar‐40Ar chronology of the enstatite chondrite parent bodies. (4th March 2014) - Hopp, Jens; Trieloff, Mario; Ott, Uli; Korochantseva, Ekaterina V.; Buykin, Alexey I.
Abstract Ar‐Ar isochron ages of EL chondrites suggest closure of the K‐Ar system at 4.49 ± 0.01 Ga for EL5 and 6 chondrites, and 4.45 ± 0.01 Ga for EL3 MAC 88136. The high‐temperature release regimes contain a mixture of radiogenic 40Ar* and trapped primordial argon (solar or Q‐type) with 40Ar/36ArTR ~ 0, which does not affect the 40Ar budget. The low‐temperature extractions show evidence of an excess 40Ar component. The 40Ar/36Ar is 180–270; it is defined by intercept values of isochron regression. Excess 40Ar is only detectable in petrologic types >4/5. These lost most of their primordial 36Ar from low‐temperature phases during metamorphism and retrapped excess 40Ar. The origin of this excess 40Ar component is probably related to metamorphic Ar mobilization, homogenization of primordial and in situ radiogenic Ar, and trapping of Ar by distinct low‐temperature phases. Ar‐Ar ages of EH chondrites are more variable and show clear evidence of a major impact‐induced partial resetting at about 2.2 Ga ago or alternatively, prolonged metamorphic decomposition of major K carrier phases. EH impact melt LAP 02225 displayed the highest Ar‐Ar isochron age of 4.53 ± 0.01 Ga. This age sets a limit of about 25–45 Ma for the age bias between the K‐Ar and U‐Pb decay systems.